Rancang Bangun Game Edukasi Biologi untuk Peningkatan Pemahaman Materi Genetika - Fahrudin Mukti Wibowo; Muhammad Alfi Ramadhani (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2019)
Education systems in schools today are generally still oriented to the material media books and verbal material delivery by the teacher. This problem raises the lack of understanding and lack of interest of students in understanding material, especially in Biology chapter Genetics. The learning media provided by the teacher are felt to be lacking to support the achievement of maximum student learning achievement. Therefore an interesting learning media is needed that aims to foster students 'interest in learning and increase students' understanding of genetic material. Alternative learning media that can be used is with educational games. In the process of developing this educational game using the waterfall method. The selection of the waterfall method is because the process of making each stage is systematic, meaning that each stage is interrelated so that it can facilitate the making of the system. The results of this study were in the form of an educational game "The Adventure of Cali-Cali" which was tested on students to find out the improvement in learning achievement. From the data obtained at the pretest results show that students still do not understand the genetic material provided by the teacher. This is evidenced by as many as 90.3% of students who have not met the Minimum Completion Criteria (KKM). Then the treatment game was given when the posttest showed that as much as 6.50% of students did not meet the KKM. The comparison of the results of the pretest and posttest showed an increase in student learning achievement which increased to 83.8%.